Revealed Preferences for Property Taxes: An Empirical Study of Perceived Tax Incidence - Moomau, Pamela H.; Morton, Rebecca B. (The Review of Economics and Statistics, 1992)
Pamela H. Moomau, Rebecca B. Morton, Revealed Preferences for Property Taxes: An Empirical Study of Perceived Tax Incidence, The Review of Economics and Statistics, Vol. 74, No. 1 (Feb., 1992), pp. 176-179